Biostimulation effects of linseed and citrus oils on growth, antioxidant enzymes activity, metabolic changes and water relations of Khaya senegalensis seedlings under drought stress (Journal of Pharmaceutical Negative Results, 2022)
This study aim to use environmentally friendly material (Linseed and citrus oils) to reduce the harmful effect of water deficit on Khaya senegalensis plant due to its economic importance as a source of wood in addition to many uses of alternative medicine. Therefore, Khaya senegalensis plants were grown in green house with three irrigation intervals (5, 7 and 9 days) and oils foliar spray as linseed oil (Lin) at (0, 5, 7%) and citrus oils at (0, 1, 2%). The results indicated that the 9 days irrigation interval gave the lowest values of the most studied growth parameters, water relations (relative water content (RWC%), water retention capacity (WRC) and membrane stability index(MSI%), photosynthesis pigments, chlorophyll stability index (CSI%), minerals content, total free amino acid while increased values of electrolyte leakage (EL%), total sugar, total phenol, and antioxidant enzymes activities(Catalase (CAT), Peroxidase (POX), Superoxide dismutase (SOD)). Both oils treated especially linseed oil, at 7% increased values of all parameters and chemical composition compared with untreated plants plus different irrigation intervals, except EL% was decreased. The data provided evidence that linseed and citrus oils treatment reduces the adverse effect of water deficit on Khaya senegalensis plants and can play a role in providing stress tolerance.